A Comparison of Murottal Al-Qur'an and Classical Music Therapy on Women’s Anxiety Levels During Early Labor at Muhammadiyah Palembang Hospital: A Comparison of Murottal Al-Qur'an and Classical Music Therapy on Women’s Anxiety Levels During Early Labor at Muhammadiyah Palembang Hospital - Kurniawan Kurniawan; Okta Dwi Irjani; Noviyanti Goei; Ahmad Ghiffari (Jurnal Surya Medika (JSM), 2025)
The prevalence of clinical anxiety disorders during the first periods of delivery was notable, with 15.2% of women experiencing any anxiety disorder antenatally worldwide. This study investigated the soothing effect of listening to Murottal Qur’an and classical music on pregnant women. A quasi-experimental design was applied, specifically a two-group pretest and posttest design, involving patients at Muhammadiyah hospital. The sample consisted of 36 respondents who met the specified inclusion and exclusion criteria and were interviewed to determine their mental health levels, categorized as not anxious, mild, moderate, or serious anxiety. Statistical software was used to analyze the effectiveness of Al-Qur’an murottal therapy and classical music through the Wilcoxon test and Mann-Whitney test. The anxiety levels for the Murottal group were initially 3.39 and decreased to 1.83, while the music group started at 2.83 and remained at 2.28. These findings indicate that Al-Qur’an murottal therapy is more effective than classical music in reducing anxiety levels in mothers during the initial stage of childbirth